THE INFLUENCE OF USING FISHBONE ISHIKAWA TECHNIQUE TO IMPROVE STUDENTS’ WRITINGSKILL OF THE FIRST SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM TEACHER TRAINING AND EDUCATION FACULTY UNIVERSITAS BANDAR LAMPUNG - Aulia Safitri; Deri Sis Nanda (Universitas Bandar Lampung, 2016)
The aims of the research was to find out if there is influence of using Fishbone Ishikawa to improve students’ writing skill of the first semester students of English Education Study Program Faculty of Teacher Training and Education Bandar Lampung University. This research is an experimental research design which measure the score of pre-test and post-test as an instrument to know whether there is an influence of fishbone ishikawa or not. The subject of this research is consisted of 50 students which are divided into experimental class and control class. The data is analyzed by using t-Test for two group design. The result showed that the students’ mean score of experimental and Control class in post-test is significantly different. It shows the t-value is 4.67, and it showed that t-value is higher than p-value 0.05 (2.0106) and 0.01 (2.6822). Therefore, null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. It means that there is an impact of using fishbone ishikawa technique to improve students’ writing ability. These findings suggest that there is influence of using of Fishbone Ishikawa technique in improving students’ writing ability of the first semester students of English Education Study Program Faculty of Teacher Training and Education Bandar Lampung University. In conclusion, Fishbone Ishikawa technique could be applied in teaching English, especially in writing skill.